Detection of Gases and Collapses in Underground Mines Using Wsn - Soto-Gomez, J (2011)
Safety is an element of extreme priority in mining operations, currently many traditional mining countries are investing in the implementation of wireless sensors capable of reducing the number of accidents; through early warning signs to prevent injuries, dead and significant economic losses. The application of sensors capable of measuring in real time variables of interest, promises to be of great impact on safety for mining industry. In this publication analyzed the main causes of accidents in coal mining underground, the technical issues to implement an efficient monitoring program of collapses and gases into underground mining. Issues related with the advantages, management and mine operations are discussed, including the analysis of Benefit, Opportunity, Cost and Risk. The publication will focus on coal mines, because these seem to be most accident prone underground mining environments. However, many of the reported results can be extrapolated to other mining activities. © 2011 IEEE.